Inclusiveness revisited: Assessing inclusive businesses in South African agriculture - (:unkn) unknown (My University, 2019)
Inclusive businesses are complex partnerships between commercial entities and smallholders/low-income communities, to include the latter in commercial agricultural value chains. IBs offer income opportunities for both partners, but are also regarded as empowering the smallholders/communities. To date, IB inclusiveness has been assessed mainly through basic quantitative measurements. However, these measures neglect the complexities of the overall value creation process, and of the inclusion of the beneficiaries within this process. This paper aims at providing a more holistic methodology by assessing the level of inclusiveness based on four dimensions: ownership, voice, risk and reward. Case studies in South Africa show that inclusion of low-income communities lags behind the intended level. Lack of financial resources and skills, reinforced by power imbalance, result in smallholder ownership being limited to land, the community's voice being compromised, risk being transferred to the smallholder communities and rewards being disappointing for the beneficiaries.
Keywords: African Research